Shear ram speed characterization for copper wire bond shear test - Zaliman, Sauli, Prof. Madya Dr.; Retnasamy, Vithyacharan; Ahmad Husni, Mohd Shapri; Norazeani, Abdul Rahman; Wan Mokhzani, Wan Norhaimi; Taniselass, Steven; Abdul Halis, Abdul Aziz (Trans Tech Publications, Switzerland., 2013)
Link to publisher's homepage at http://www.ttp.net/